Comparison of Cuckoo Search Algorithm and Perturb & Observe Algorithm in Positive Elementary Superlift Luo Converter for Motor Drive Application - T.V.Narmadha , M.Evanjalin Maria Florida, J. Kavitha (International Journal of Modern Agriculture, 2021)
Positive Output Elementary Super-lift Luo Converter is the DC-DC Converter, has the voltage lifting techniques. This plays vital role in designing electronic circuit. The voltage output variation is in geometric progression. To get static and dynamic control cuckoo search algorithm is used. Solar PV is used to reduce the effects of parasitic components which has an impact in output voltage and power transfer. The output from the converter is used for Motor drive application.